Trend and Pattern of Expenditure on Fisheries Extension in India: Implications for Policy - V.K. Sajesh , A. Suresh , A.K. Mohanty , M.V. Sajeev , S. Ashaletha , K. Rejula; C.N. Ravishankar (Indian Journal of Extension Education, 2018)
A vibrant extension system is essential to address the emerging challenges in the fisheries sector and to augment its development. Performance of such a system depends on policy support in terms of budgetary allocation. An attempt is made to analyse the pattern of expenditure on fisheries extension based on information collected from combined revenue and finance account of Comptroller and Auditor General of India (1974- 2014). Trends in expenditure (Centre plus State governments) on fisheries extension point to its steady rise except for the reversals during 1990-91 to 1994-95 and 2002-03 to 2004-05. Though the trend is impressive, it appears to be thinly spread, considering the vast coast line and increasing aquaculture. In the past decade (2005-06 to 2013-14), growth rate in extension expenditure (Centre plus State governments) in fisheries sector was found to be 4%. As a policy prescription, the study calls for increased expenditure on fisheries extension.